Toleransi Beragama dalam Pandangan Hadis untuk Ketenangan Beribadah di Nusantara: Studi Takhrij dan Syarah - Alif Fadilah; Dadang Darmawan; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about religious tolerance. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about religious tolerance in the history of Bukhari no. 38. The results and discussion of this study indicate that the status of the hadith is of authentic quality that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Bukhari no. 38 relevant to be used as motivation to develop religious tolerance in Indonesia.